Hegel on history - McCarney, Joe. (London ; New York : Routledge, 2000)
Hegel's Introduction to the Philosophy of History remains one of the most profound and influential books on the philosophy of history. In clear and cogent terms this book:* examines the ideas and arguments of the Introduction to the Philosophy of History* explains key concepts of Hegel's system, a knowledge of which is essential for fully understanding his philosophy of history* assesses the continuing relevance of Hegel to the contemporary debate about the nature of history.
pt. 1. Philosophical foundations -- pt. 2. The course of history.
Includes bibliographical references (pages 221-228) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831 -- Contributions in philosophy of history; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831; History -- Philosophy; Histoire -- Philosophie; HISTORY -- General; History -- Philosophy